The eight inter-Asian corn improvement workshop (Bangkok, 1972)
This workshop includes special presentations about physiological aspects of grian yield of maize; Effect of different plant populations and combinations of N P K on the Gian Yeild of improved maize under late sown condition in the Kathhmandu Valeey, Nepal;...
Keywords: Agriculture,Corn,Plants, cultivated; Research